Long term pregnancy outcome following amniocentesis and chorionic villous sampling. (18th April 2012) - Mehta, M; Down, C; Sau, A
Abstract : Aim: To investigate the long term pregnancy outcome following mid trimester amniocentesis and chorionic villous sampling in the first trimester. Methods: Pregnancy outcome data was retrieved from hospital database (Astraia software gmbh and Terranova Healthware) for all invasive procedures done by a single operator between 2008-2010. Outcomes of 84 cases of amniocentesis and 24 chorionic villous samplings (CVS) were compared with controls. Results: The main indications for amninocentesis (n=84) procedure included: screen positive on combined screening (78.5%), early onset IUGR (1%), congenital anomalies found on nuchal or anomaly scan (16.6%), prenatal diagnosis for haemoglobinopathies (2%) and maternal request (1%). 16 cases were excluded from further analysis due to presence of congenital anomalies, early onset IUGR and termination of pregnancy (TOP) due to HbSS. Indications of CVS (n=24) included: screen positive on combined screening (79.5%), congenital anomalies (8%) and prenatal diagnosis (12.5%). 2 cases had TOP due to Turner's syndrome. 19 cases were analysed (after excluding congenital anomalies and TOP cases) for long-term pregnancy outcome. In control group (n=90) all cases delivered beyond 36 weeks of gestation as compared to 66 out of 68 (97%; P=0.19) cases of mid trimester amniocentesis and 17 out of 19 cases (89.5%; P < 0.05) in CVS group. Conclusion: We report that patients undergoing amniocentesis have similar long-term pregnancy outcomes as matched controls; with patients undergoing chorionic villous sampling were more likely to deliver prior to 36 weeks.